Etiology Profile of Lower Gastrointestinal Bleeding - Masrul Lubis; Lukman Hakim Zain (The Indonesian Society for Digestive Endoscopy, 2012)
Background: Lower gastrointestinal bleeding (LGIB) is still a significant health problem since the unknown etiology had not existed until now. Similar condition occurs at Adam Malik Hospital. No data about the etiology of LGIB has been defined. Therefore, this study was aimed to recognize the etiology profile of LGIB at Adam Malik Hospital, Medan. Method: A retrospective descriptive study was conducted on medical records of patients who had undergone lower gastrointestinal tract endoscopy (colonoscopy) at Adam Malik Hospital, Medan between January 2009 and December 2010 based on their complaint of hematochezia. Data was analyzed using SPSS version 19. The data was categorized based on subjects’ age, sex and etiology of their hematochezia. Results: There were 116 patients consisted of 61 (52.6%) males and 55 (47.4%) females with mean age of 50.52 (17-84) years. The colonoscopy revealed 52 (44.7%) cases of hemorrhoidal varices, 17 (14.7%) cases of rectal carcinoma, 17 (14.7%) normal endoscopic results, 8 (6.9%) cases of sigmoid carcinoma, 8 (6.9%) of proctitis, 6 (5.1%) cases of colitis, 4 (3.5%) cases of colon carcinoma, and 4 (3.5%) cases of rectosigmoid carcinoma. Conclusion: This study found that hemorrhoidal varices is the most common etiology of LGIB. Keywords: LGIB, colonoscopy, hemorrhoids